Psychoeducation Program: Parent-Child Mediation to Reduce the Intensity of Gadget Use in Early Childhood - Destariza Akbar Dwi Pamungkas; Ika Oktafia; Galang Sukma Bangsa; The, Aurelia Tiffany Hartanto; Hendry Martin Kawengian; Doddy Hendro Wibowo (Devotion : Jurnal Pengabdian Psikologi, 2025)
The use of digital gadgets presents both opportunities and challenges for early childhood development. While gadgets can facilitate access to information, improve communication, expand social networks, and foster creativity, improper or unsupervised use may lead to adverse effects. This community service activity aimed to provide psychoeducation to parents and guardians of students at TK Kartini Banyubiru regarding the impact of gadget use on young children. The intervention was delivered in the form of a psychoeducational session, attended by 48 participants. The results indicated that participants responded positively to the session, reporting increased awareness and new insights into effective parenting practices. This activity contributed to enhancing parents' understanding of how to appropriately manage and supervise their children's gadget use, thereby helping to mitigate potential negative consequences.